Thermal effects on the switching kinetics of silver/manganite memristive systems - Stoliar, Pablo Alberto (2014)
We investigate the switching kinetics of oxygen vacancy (Ov) diffusion in La(5/8-y)Pr(y)Ca(3/8)MnO(3)-Ag (LPCMO-Ag) memristive interfaces by performing experiments on the temperature dependence of the high resistance state under thermal cycling. Experimental results are well reproduced by numerical simulations based on thermally activated Ov diffusion processes and fundamental assumptions relying on a recent model proposed to explain bipolar resistive switching in manganite-based cells. The confident values obtained for activation energies and the diffusion coefficient associated to Ov dynamics constitute a validation test for both model predictions and Ov diffusion mechanisms in memristive interfaces.